2017
DOI: 10.1080/09506608.2017.1296605
|View full text |Cite
|
Sign up to set email alerts
|

Present and future thermal interface materials for electronic devices

Abstract: Packaging electronic devices is a growing challenge as device performance and power levels escalate. As device feature sizes decrease, ensuring reliable operation becomes a challenge. Ensuring effective heat transfer from an integrated circuit and its heat spreader to a heat sink is a vital step in meeting this challenge. The projected power density and junction-toambient thermal resistance for high-performance chips at the 14 nm generation are >100 Wcm −2 and <0.2 °CW −1 , respectively. The main bottleneck in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
170
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(171 citation statements)
references
References 110 publications
(178 reference statements)
1
170
0
Order By: Relevance
“…The needs for energy consumption and dissipation have triggered condensed interests in nanoscale materials and devices that hold potential applications for better energy conversion and harvesting. An example is the integrated electronic circuits in which power dissipating issue has recently become the bottleneck . With further miniaturization of modern electronics, the high power energy accumulated heat waste has increased the operating temperature to a high level where thermal management and heat dissipation become crucial for the performance of the devices .…”
Section: Thermal‐related Applicationsmentioning
confidence: 99%
“…The needs for energy consumption and dissipation have triggered condensed interests in nanoscale materials and devices that hold potential applications for better energy conversion and harvesting. An example is the integrated electronic circuits in which power dissipating issue has recently become the bottleneck . With further miniaturization of modern electronics, the high power energy accumulated heat waste has increased the operating temperature to a high level where thermal management and heat dissipation become crucial for the performance of the devices .…”
Section: Thermal‐related Applicationsmentioning
confidence: 99%
“…A good TIMs candidate should possess properties of high thermal conductivity, providing good surface contact, low thermal internal resistance, and good mechanical properties. The application of TIMs is leaned toward the exploration of nanomaterials, such as CNTs and graphene . In this study, CNTs, graphene, and graphite are highlighted.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
“…The coating technique that cover on top of VACNT before complete the TIMs assembly has gained attention from other researchers when dealing with VACNT and found that the coating will help on reducing thermal contact resistance, increasing surface contact between VACNT and heat sink, and maintaining the optimum thermal conductivity . In addition, the reliability of the thermal performance of TIMs is an important factor to be considered.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
See 2 more Smart Citations